Predictors of Inflammation in Response to Anthracycline-Based Chemotherapy for Breast Cancer - Mills, Paul J. (2007)
Although chemotherapy for breast cancer can increase inflammation, few studies have examined predictors of this phenomenon. This study examined potential contributions of demographics, disease characteristics, and treatment regimens to markers of inflammation in response to chemotherapy for breast cancer. Thirty-five women with stage I - III-A breast cancer (mean age 50 years) were studied prior to cycle 1 and prior to cycle 4 of anthracycline-based chemotherapy. Circulating levels of inflammatory markers with high relevance to breast cancer were examined, including C-reactive protein (CRP), tumor necrosis factor-α (TNF-α), Interleukin-1 receptor antagonist (IL1-RA), vascular endothelial growth factor (VEGF), soluble intercellular adhesion molecule-1 (sICAM-1), Interleukin- (IL-6), soluble P-selectin (sP-selectin), and von Willebrand factor (vWf). Chemotherapy was associated with elevations in VEGF (p≤0.01), sICAM-1 (p≤0.01), sP-selectin (p≤0.02) and vWf (p≤0.05). Multiple regression analysis controlling for age and body mass index (BMI) showed that higher post-chemotherapy levels of inflammation were consistently related to higher pre-chemotherapy levels of inflammation (p’s ≤0.05) as well as to certain disease characteristics. Post-chemotherapy IL-6 levels were higher in patients who had larger tumors (p≤0.05) while post-chemotherapy VEGF levels were higher in patients who had smaller tumors (p≤0.05). Post-chemotherapy sP-selectin levels were highest in women who had received epirubicin, cytoxan, 5fluorouracil chemotherapy (p≤0.01). These findings indicate that chemotherapy treatment can be associated with elevations in certain markers of inflammation, particularly markers of endothelial and platelet activation. Inflammation in response to chemotherapy is most significantly related to inflammation that existed prior to chemotherapy but also potentially to treatment regimen and to certain disease characteristics.